ZONASI FISIOMORFOHIDRO DI JAWA BARAT DENGAN MENGGUNAKAN APLIKASI SIG - Setiawan, Iwan; Rohmat, Dede (Indonesia University of Education, 2011)
Rainfall data has collected from rain station which is attached by certain institution like Meteorology Climatology and Geophysics Agency or another institution to fulfill the need of rainfall data at certain location, such as paunch otority, communication and transportasion agency etc. The problem: is the existing rain station distribution has covers rain parameters such as altitude, morphology, and rain distribution, with the result that every parameters represented for every parameters? Here by the objectives of this research is to mapping and analiyzing rain station distribution wich is related to those parameters. If those three map overlay then produce fisiomorphohydro zone. Overlay of three map with GIS Aplication is used to analysis. The result of this research shows that West Java have 90 zone of fisiomorphohydro. The composite map shows that West Java hasn’t even rain station distribution. Based on overlay of fisiomorhohydro zonation map and rainfall station distributions of West Java, then we find out that there are many zonation which hasn’t representative rain station. Keywords: zonation, fisiomorfohydro, GIS Application, fisiography,topography,rainfal, isohyet, rain intensity, distribution, rain station